1976
DOI: 10.1080/05698197608982795
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Analysis of High-Contact-Ratio Spur Gears

Abstract: A computer program has been developed to design external spur gears having normal contact ratios (<2.0) and high contact ratios ( 2 2.0). This program has been used to study the efects of changes in some gear parameters on several performance factors of highcontact-ratio gears. The results are compared with those for the equivalent normal-contact-ratio gears.The study shows that a high-contact-ratio gear obtained by increasing the addendum of an equivalent normal-contact-ratio gear will have lower bending and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…This r a n k i n g o f t h e gear losses i s cons i s t e n t w i t h what Staph found i n Ref. 16 even though t h e magnitudes a r e n o t the same. Since Staph d i d n o t consider r o l l i n g o r windage losses h i s l o s s estimate f o r gear M was much lower than shown here.…”
Section: An O I L V I S C O S I T Y O F 30 Cp Was Selected O F T H Ementioning
confidence: 79%
“…This r a n k i n g o f t h e gear losses i s cons i s t e n t w i t h what Staph found i n Ref. 16 even though t h e magnitudes a r e n o t the same. Since Staph d i d n o t consider r o l l i n g o r windage losses h i s l o s s estimate f o r gear M was much lower than shown here.…”
Section: An O I L V I S C O S I T Y O F 30 Cp Was Selected O F T H Ementioning
confidence: 79%
“…44 performed an experiment, which indicated that the surface temperature for a curved-face-width spur gear was close to maximum surface temperature calculated for the similar standard spur gear. Staph 45 suggested that a gear with high-contact ratio obtained by increasing the addendum of an equivalent normal-contact-ratio gear, will have lower bending and compressive stresses. Walton et al.…”
Section: Rudimentary and Advanced Design Features Of Polymer And Polymentioning
confidence: 99%
“…43 Andrei et al 44 performed an experiment, which indicated that the surface temperature for a curved-face-width spur gear was close to maximum surface temperature calculated for the similar standard spur gear. Staph 45 suggested that a gear with high-contact ratio obtained by increasing the addendum of an equivalent normalcontact-ratio gear, will have lower bending and compressive stresses. Walton et al 46 found that the increase in the center distance of a gear pair had little effect on the efficiency but, when the center distance reduced, the efficiency deteriorated with the increasing speed due to tooth interference.…”
Section: Rudimentary and Advanced Design Features Of Polymer And Polymentioning
confidence: 99%
“…In the past few decades, most of research on HCRG has mainly been concentrated on tooth load sharing, stress analysis, and tooth profile modification. Staph [4] discussed the effects of gear parameters on several performance factors of HCRG and gave a method to tooth load sharing in HCRG. Cornell and Westervelt [1] developed a dynamic model for calculating the dynamic tooth loads and root stresses for HCRG.…”
Section: Introductionmentioning
confidence: 99%